2021
DOI: 10.1128/spectrum.00250-21
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Antibody Rapid Tests: Valuable Epidemiological Tools in Challenging Settings

Abstract: Our study provides a fresh perspective on the possible employment of SARS-CoV-2 LFA antibody tests. We developed an in-depth, large-scale analysis comparing LFA performance to enzyme-linked immunosorbent assay (ELISA) and electrochemiluminescence immunoassay (ECLIA) and evaluating their sensitivity and specificity in identifying COVID-19 patients at different time points from symptom onset.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Binomial mixed model analysis found that the test results were not significantly impacted by day of sample collection (Day 21 or 42 post vaccine dose) which is consistent with findings indicating IgG antibodies are detectable between 21 and 60 days after vaccination (21,22). Similarly, vaccine brand did not significantly impact test results, both these findings highlight that wider testing could be flexible without compromising sensitivity.…”
Section: Discussionsupporting
confidence: 77%
“…Binomial mixed model analysis found that the test results were not significantly impacted by day of sample collection (Day 21 or 42 post vaccine dose) which is consistent with findings indicating IgG antibodies are detectable between 21 and 60 days after vaccination (21,22). Similarly, vaccine brand did not significantly impact test results, both these findings highlight that wider testing could be flexible without compromising sensitivity.…”
Section: Discussionsupporting
confidence: 77%
“…Binomial mixed model analysis found that the test results were not significantly impacted by day of sample collection (Day 21 or 42 post vaccine dose) which is consistent with findings indicating IgG antibodies are detectable between 21 and 60 days after vaccination [22,23]. Similarly, vaccine brand did not significantly impact test results, both these findings highlight that wider testing could be flexible without compromising sensitivity.…”
Section: Discussionsupporting
confidence: 76%
“…There was low agreement of the SARS-CoV-2 Rapid Antibody Test (IgM) with the Elecsys Anti-SARS-CoV-2 S assay because, in general, there is a lower sensitivity for IgM compared with IgG for point-of-care lateral flow assays, as exemplified in a recent analysis of healthcare workers vaccinated with the first dose of the Pfizer vaccine and sampled 21–24 days thereafter ( 37 ). In addition, the Elecsys Anti-SARS-CoV-2 S assay preferentially detects high-affinity IgG antibodies that compete with IgM antibodies ( 23 ), contributing to the lower agreement rates with IgM results.…”
Section: Discussionmentioning
confidence: 99%